(untitled) (Physical Education, Health and Social Sciences, 2025)
Total Hip Replacement (THR) is a complex and time-consuming surgical procedure that needs close collaboration among operating room staff, still, prolonged duration of procedures due to intraoperative challenges, unanticipated complications and anatomical complexity can have significant impact on staff. Extended duration can contribute to increase physical and mental fatigue, elevated stress and reduced cognitive response which may impact outcomes. The purpose of this study is to evaluate how extended THR operations affect the regular management and mental well-being of theater employees, such as anesthetists, surgeons, scrub nurses, circulation nurses, and other support workers. The study investigates the effects of prolonged surgical length on healthcare workers’ coping strategies, emotional flexibility, stress levels, and workload distribution in the operating room. Operational theater personnel in high-volume orthopedic units were surveyed quantitatively and qualitatively as part of a mixed-methods approach. To determine how long procedures affected staff well-being, standardized psychological stress and tiredness measurement instruments were used. Workflow disruptions and efficiency indicators were also looked at in order to understand how intraoperative issues affect daily management. Statistical analysis was used to look at correlations between the length of surgery and reported levels of stress, fatigue, and performance changes. Results shows that prolonged surgical time increases the level of psychological stress, overall discomfort, mental and physical exhaustion, participant reported more emotional strained, feeling trouble focusing and coordination among staff to make workflow which results in poor productivity and high error rates. A lack organized recovery time was also mentioned by numerous employees that may worsen the situation. The research highlights the pressing need for services like mental health assistance, coordinated break schedules, ergonomic improvements, and rotational staffing. By implementing these strategies, staff resilience, productivity, and a healthy workplace can all be increased, improving surgical outcomes.